Home, Sweet, Sweet Home - Ojo-Ade, Femi (University Press Plc, 1987)
Ade is requested by his father to return to his homeland after spending twelve years in America. On getting home he is totally bewildered by the changes which have taken place during his absence. Ade finds himself faced with a terrible dilemma$1! =s
Keywords: Juvenile Fiction